Triazole-curcuminoids: A new class of derivatives for 'tuning' curcumin bioactivities?. Issue 2 (15th January 2016) - Caprioglio, Diego; Torretta, Simone; Ferrari, Maila; Travelli, Cristina; Grolla, Ambra A.; Condorelli, Fabrizio; Genazzani, Armando A.; Minassi, Alberto
Graphical abstract: Abstract: Curcumin is a unique blend of pharmacophores responsible for the pleiotropy of this natural pigment. In the present study we have replaced the 1, 3-dicarbonyl moiety with a 1, 2, 3-triazole ring to furnish a new class of triazole-curcuminoids as a possible strategy to generate new compounds with different potency and selectivity compared to curcumin. We obtained a proof-of-principle library of 28 compounds tested for their cytotoxicity (SY-SY5Y and HeLa cells) and for their ability to inhibit NF-κB. Furthermore, we also generated 1, 3-dicarbonyl curcuminoids of selected click compounds. Triazole-curcuminoids lost their ability to be Michael's acceptors, yet maintained some of the features of the parent compounds and disclosed new ones. In particular, we found that some compounds were able to inhibit NF-κB without showing cytotoxicity, while others, unlike curcumin, activated NF-κB signalling. This validates the hypothesis that click libraries can be used to investigate the biological activities of curcumin as well as generate analogs with selected features.